1997
DOI: 10.1523/jneurosci.17-12-04873.1997
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Medullary Gustatospinal Pathways In a Catfish: Possible Neural Substrates for Taste-Mediated Food Search

Abstract: Taste and tactile fibers in the facial nerve of catfish innervate extraoral taste buds and terminate somatotopically in the facial lobe (FL)-a medullary structure crucial for gustatory-mediated food search. The present study was performed to determine the neural linkages between the gustatory input and the spinal motor output. Spinal injections of horseradish peroxidase (HRP) label spinopetal cells in the octaval nuclei, the nucleus of the medial longitudinal fasciculus, and reticulospinal neurons (Rsps) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
0
12
1
Order By: Relevance
“…In some teleosts, the reticulospinal neurons exhibit a clear segmentation: They are distributed in 14 clusters that are postulated to lie in 8 metameric segments (Kanwal and Finger, 1997). However, a similar metameric pattern was not reported in the reticulospinal system of the dogfish (Smeets and Timerick, 1981;Timerick et al, 1992), and we have not found a distribution of ChAT-ir reticular cells in groups different from the cell groups reported by those authors.…”
Section: Segmental Organization Of Cholinergic Nuclei Of the Braincontrasting
confidence: 47%
“…In some teleosts, the reticulospinal neurons exhibit a clear segmentation: They are distributed in 14 clusters that are postulated to lie in 8 metameric segments (Kanwal and Finger, 1997). However, a similar metameric pattern was not reported in the reticulospinal system of the dogfish (Smeets and Timerick, 1981;Timerick et al, 1992), and we have not found a distribution of ChAT-ir reticular cells in groups different from the cell groups reported by those authors.…”
Section: Segmental Organization Of Cholinergic Nuclei Of the Braincontrasting
confidence: 47%
“…Our neomycin data, however, are not definitive regarding capture swim modality because these swims remain well formed in the Light + Neomycin condition. Contributions to the control of capture swims by olfactory and gustatory senses (Caprio, 1978; Kanwal and Finger, 1997; Friedrich et al, 2004; Gardiner and Atema, 2007) or tactile interactions (Patterson et al, 2013) remain a possibility.…”
Section: Discussionmentioning
confidence: 99%
“…A possible source of gustatory input to the reticulospinal system has been described in the channel catfish, Ictalurus punctatus [Kanwal and Finger, 1997]. Most other available data concerns possible overlap between escape and prey capture circuitry [reviewed in Batty and Domenici, 2000], although the evidence for escape circuitry playing a major role in prey capture locomotion is not compelling.…”
Section: Existing Data On the Neural Control Of Prey-capture Locomotionmentioning
confidence: 99%